A novel value-based scoring system for endoscopic ultrasound-guided drainage of pancreatic fluid collections: a single-centre comparative study of plastic and lumen-apposing metal stents (NOVA study). Issue 2 (February 2021) - Parihar, Vikrant; Basir, Yasir; Nally, Deirdre; Mellotte, Gregory; Manoharan, Thilagraj; Walker, Caroline; Ridgway, P.F.; Conlon, K.C.; Breslin, Niall; Harewood, Gavin C.; Ryan, Barbara M.
Abstract : Objective: Healthcare resources are finite. Value in healthcare can be defined as patient health outcomes achieved per monetary unit spent. Attempts have been made to quantify the value of luminal endoscopy, but there is little in the medical literature describing the value of the complex therapeutic endoscopic activity. This study aimed to characterise the value of endoscopic ultrasound (EUS)-guided drainage of pancreatic fluid collections (PFCs) with either plastic or lumen-apposing metal stents (LAMSs). Methods: This is a single-centre, retrospective–prospective comparative study of 39 patients, who underwent EUS-guided PFC drainage between 2009 and 2018. Procedure value was calculated using the formula Q/(T/C), where Q is the quality of procedure adjusted for complications, T procedure duration and C is the complexity adjustment. Quality and complexity were estimated on a 1–4 Likert scale based on the American Society for Gastrointestinal Endoscopy criteria. Time (in minutes) was recorded from the patient entering and leaving the procedure room. Endoscopy time calculated from procedure time was considered a surrogate marker of cost as individual components of procedure cost were not itemized. Results: Of 39 identified patients who underwent EUS-guided PFC drainage, 11 received double pigtail plastic stents (DPPSs) and 28 received LAMSs. The two groups were comparable in age, gender and aetiology. Nearly 40% of the LAMS interventions were considered high value but only 11% of the plastic stent interventions achieved the same. The difference predominantly was due to a higher rate of complications and longer procedure time. Conclusion: In this single-centre study, EUS-guided PFC drainage using LAMS was found to be a higher value procedure compared to the use of DPPS.